Cell powered biobots and more perspectives for IJB - Chua, Chee Kai (2018)
At the end of 2016, International Journal of Bioprinting (IJB) is able to estimate its first mock impact factor. Based on one issue published in 2015, the 2016 mock impact factor for IJB is calculated to be 6, excluding self-citations! This result is surprising, impressive and encouraging. However, this is just a beginning and more and more quality articles and reviews are needed in order to maintain it.